2015
DOI: 10.1159/000430166
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Recombining Binding Protein Suppressor of Hairless (RBPJ) Impairs the Growth of Prostate Cancer

Abstract: Background/Aims: Notch signaling pathway regulates cancer cell growth. RBPJ is a key transcription factor downstream of Notch receptor activation, whereas the role of RBPJ in carcinogenesis of prostate cancer is ill-defined. Methods: Here, we evaluated the effects of RBPJ inhibition on the growth of prostate cancer cells. We knocked down RBPJ in prostate cancer cells by a short hairpin interfering RNA (shRNA). We measured cell growth by an MTT assay. We analyzed the levels of cell-cycle-associated proteins by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Specifically, CSL silencing in MDA-MB-231 human breast cancer and DG75 Burkitt lymphoma cells enhanced tumor growth, with c-MYC-and NF-KB-dependent increases in cell survival. However, an opposite conclusion was suggested by other studies with cultured cancer cell lines, including one that was also with MDA-MB-231 cells (55)(56)(57). Thus, the possibility of distinct roles of NOTCH and CSL in specific cancer types needs further assessment in the context of their cells of origin and tumor microenvironment.…”
Section: Discussionmentioning
confidence: 83%
“…Specifically, CSL silencing in MDA-MB-231 human breast cancer and DG75 Burkitt lymphoma cells enhanced tumor growth, with c-MYC-and NF-KB-dependent increases in cell survival. However, an opposite conclusion was suggested by other studies with cultured cancer cell lines, including one that was also with MDA-MB-231 cells (55)(56)(57). Thus, the possibility of distinct roles of NOTCH and CSL in specific cancer types needs further assessment in the context of their cells of origin and tumor microenvironment.…”
Section: Discussionmentioning
confidence: 83%
“…This gene displays frequent deletions or mutations in SCC4748. RBPJ encodes a transcriptional factor regulating Notch signaling pathway, which has been shown to be an effective therapeutic target in various tumours454950. By using this large sample size, we generated clinical background-related mutational signatures in ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal development is one of the key and pivotal factors regulating the differentiation and proliferation of neural progenitor cells. The expression of the RBPJ gene in lung and prostate cancer cells was previously silenced by Lv et al (46) and Xue et al (47), and the results suggested that the downregulation of RBPJ expression leads to a significant decrease in the growth of cancer cells, which suggests that RBPJ serves a downstream role in the Notch signaling pathway and appears to be essential for the functional activation of Notch signaling.…”
Section: Discussionmentioning
confidence: 93%